A new round of rescheduling? - Armin Gutowski (Intereconomics, 1986)
The danger that the foreign indebtedness of developing countries will again come to a head has by no means been banished. Prof. Gutowski outlines proposals for concerted action by commercial banks, the World Bank and regional development banks which could help to prevent the outbreak of a new crisis.
Keywords: 330; Indebtedness